2006
DOI: 10.1016/j.jpubeco.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Building and managing facilities for public services

Abstract: We model alternative institutional arrangements for building and managing facilities for provision of\ud public services, including the use of the Private Finance Initiative (PFI), by exploring the effects on\ud innovative investment activity by providers. The desirability of bundling the building and management\ud operations is analyzed, and it is considered whether it is optimal to allocate ownership to the public or the\ud private sector. We also examine how the case for PFI is affected by the (voluntary or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
208
1
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(232 citation statements)
references
References 8 publications
6
208
1
10
Order By: Relevance
“…The same logic works in the cases below. Council) is on lease to the private partner for a peppercorn rent for the whole duration of the project, and will revert to the Council on expiry of the contract or earlier termination [3].…”
Section: Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The same logic works in the cases below. Council) is on lease to the private partner for a peppercorn rent for the whole duration of the project, and will revert to the Council on expiry of the contract or earlier termination [3].…”
Section: Examplesmentioning
confidence: 99%
“…One of the issues, rather well studied in the literature, is whether some or all tasks within one, typically infrastructure, project should be delegated to a private partner (Bennett and Iossa, 2006;Martimort and Pouyet, 2008; Maskin and Tirole, 2008; Chen and Chiu, 2010). Such an "unbundling" view neglects contributions by the partners that cannot be defined as a part of the project, for example, improvements in efficiency due to knowledge spillovers through collaboration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the issues, rather well studied in the literature, is whether some or all tasks within one, typically infrastructure, project should be delegated to a private partner (Bennett and Iossa, 2006;Martimort and Pouyet, 2008; Maskin and Tirole, 2008; Chen and Chiu, 2010). Such an "unbundling" view neglects contributions by the partners that cannot be defined as a part of the project, for example, improvements in efficiency due to knowledge spillovers through collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that bundling is preferable if the quality of the service can be well specified (and therefore contracted upon) while the quality in the building stage is less easily observable. Bennett and Iossa (2006) also analyze the choice between traditional service provision (unbundling) and PPP (bundling). However, they differ from Hart (2003) by considering different ownership structures and by assuming that there is only one kind of investment in the building stage.…”
Section: Introductionmentioning
confidence: 99%